2017
DOI: 10.17712/nsj.2017.2.20160455
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal network models of epileptogenesis

Abstract: Epilepsy is a chronic neurological condition, following some trigger, transforming a normal brain to one that produces recurrent unprovoked seizures. In the search for the mechanisms that best explain the epileptogenic process, there is a growing body of evidence suggesting that the epilepsies are network level disorders. In this review, we briefly describe the concept of neuronal networks and highlight 2 methods used to analyse such networks. The first method, graph theory, is used to describe general charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…It has become evident that epilepsy is a network phenomenon and even focal epilepsy is associated with abnormal changes in connectivity between multiple brain areas . Therefore, research on HFOs needs to be extended to extrahippocampal structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become evident that epilepsy is a network phenomenon and even focal epilepsy is associated with abnormal changes in connectivity between multiple brain areas . Therefore, research on HFOs needs to be extended to extrahippocampal structures.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 It has become evident that epilepsy is a network phenomenon and even focal epilepsy is associated with abnormal changes in connectivity between multiple brain areas. 7 Therefore, research on HFOs needs to be extended to extrahippocampal structures. If the process of epileptogenesis requires formation of a widespread network of PIN clusters, 5 pHFOs during epileptogenesis should also appear in areas outside of hippocampus (HP).…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is a chronic neurological disorder characterized by the presence of recurrent unprovoked seizures due to an imbalance between cerebral excitatory and inhibitory pathways. It is one of the most common neurological conditions affecting more than 50 million people of all ages worldwide (Abdullahi and Adamu 2017). Epileptogenesis is the process by which parts of a normal healthy brain are converted into hyperexcitant ones leading to the occurrence of recurring epileptiform events and the appearance of the first spontaneous seizure (Pitkänen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some in vitro seizures generated epileptiform activities when inhibitory synapses were blocked or excitatory synapses were enhanced (Traub et al, 1994; White, 2002). Several studies showed that epileptiform activities are related not only with unbalanced neural networks, but also with highly synchronous regimes (Uhlhaas and Singer, 2006; Andres-Mach and Adamu, 2017).…”
Section: Introductionmentioning
confidence: 99%